Long-term exposure to low frequency electro-magnetic fields of 50- and 217-Hz leads to learning and memory deficits in mice - Nooshinfar, Elaheh; Rezaei-Tavirani, Mostafa; Khodakarim, Soheila (Archives of Advances in Biosciences, 2012)
Electromagnetic field (EMF) radiation affects cellular and brain chemistry and function, resulting in deleterious effects such as free radicals formation, impaired DNA repair, reduced melatonin and blood brain barrier protection, and defects on learning and memory and other higher brain functions. In this paper the effects of low frequency EMF of 50- and 217 Hz, ranges often associated with common electronic devices such as televisions and cell phones were examined on learning and memory in adult male mice. Five groups (n=10 mice/group) of mice (1 control and 4 experimental) were initially trained for the passive avoidance (PA) test. They were then placed in devices creating EMF radiation with varying intensities (0.5 to 2 milli-Tesla, mT) and frequencies (50- and 217-Hz) for 2-weeks (16 hrs/day). Control mice received no radiation. Learning and memory was tested by the PA test and evaluated based on the following parameters: mean step through latency (STL), number of crossing (Cr#) and time in dark compartment (TDC). Results showed significant deficiencies in learning and memory in the EM-exposed mice compared to controls: mean STL decreased significantly (p<0.001) in the 50 Hz group (1 and 1.5 mT intensities). In the 217 Hz group, STL also decreased in the 0.5 and 2 mT groups (p< 0.05). There was a notable increase in mean Cr# for both groups and TDC for 50 Hz group. Results confirm that long-term exposure to EMF radiation of 50 and 217 Hz, imparts significant harmful changes on memory and learning, reiterating the need for preventive measures against such exposures.